2019
DOI: 10.1177/2333794x19835235
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the Social, Physical, and Emotional Impact of Living With Perthes’ Disease in Children and Their Family: A Mixed Methods Study

Abstract: Aim . To determine the social, physical, and emotional impact of living with Perthes’ disease on affected children and their family (caregivers). Patients and Methods . Through a mixed methods approach, we interviewed 18 parents and explored the perspectives of 12 children affected by Perthes’ disease (mean = 7.1 years, SD = ±4.1 years) using a survey tool. Thematic analysis of parents’ interviews provided an insight into disease-specific factors influencing patients and famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…The PROMIS data from the current study population suggested that 70% of children had some degree of physical limitation and 30% had normal function. Understanding the limitations induced by hip disease is important as they have negative impact on the general quality of life of these children (3,9), but whether this translates into reducing their ability to perform daily physical activity such as walking is unknown. Accelerometers were employed in the current study to measure physical activity level in children with hip disease and demonstrated that the average daily MVPA of these children is of 101±37 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PROMIS data from the current study population suggested that 70% of children had some degree of physical limitation and 30% had normal function. Understanding the limitations induced by hip disease is important as they have negative impact on the general quality of life of these children (3,9), but whether this translates into reducing their ability to perform daily physical activity such as walking is unknown. Accelerometers were employed in the current study to measure physical activity level in children with hip disease and demonstrated that the average daily MVPA of these children is of 101±37 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of the cause, the main symptoms of childhood hip disease are pain and limitations in hip joint mobility (1,2). These symptoms negatively influence the quality of life of affected children through limitations in their usual activities, including walking, running and playing with their friends (3).…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative interviews were held with parents and children to identify the key outcomes of Perthes' disease amongst families. The methods and in-depth outcomes are reported elsewhere [14].…”
Section: Qualitative Interviewsmentioning
confidence: 99%
“…10 outcomes not identified through the systematic review process were identified from qualitative interviews with parents [14] and added. The full list of the patient reported outcomes (PROs) obtained is reported in Table 2.…”
Section: Patients Reported Outcomesmentioning
confidence: 99%
“…Following a comprehensive literature search, possible ways to evaluate a qualitative measure which comprises predominantly open-ended questions and, moreover, in a manner that honors the principles of qualitative research, are explored. To aid insight into the potential issues involved, the discussion and approach are situated against one newly-designed qualitative outcome measure, developed for young children (here, aged 5–8 years old) with the pediatric hip condition of Perthes 13…”
Section: Introductionmentioning
confidence: 99%